The Effects of E-Commerce, Pocket Money, And Financial Literacy on Students’ Consumptive Behavior - Andrea Tsana Khalisha; Luh Gede Meydianawathi (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Consumptive behavior refers to the tendency of individuals to purchase goods or services excessively, driven not by need but by the desire for personal satisfaction. University students are particularly vulnerable to such behavior, especially given the ease of access to e-commerce platforms and limitations in personal financial management. Pocket money received and students’ level of financial literacy are key factors shaping their consumption patterns. This study analyzes the effects of e-commerce, pocket money, and financial literacy on the consumptive behavior of undergraduate students in the Development Economics Study Program at Udayana University. A quantitative approach was employed, using a survey of 90 respondents selected through stratified random sampling. Data were analyzed using multiple linear regression. The results show that, jointly, e-commerce, pocket money, and financial literacy significantly affect students’ consumptive behavior. Partially, e-commerce and pocket money have positive effects, whereas financial literacy has a negative effect. This indicates that higher financial literacy reduces the tendency toward consumptive behavior.